Absorption and regeneration characteristics of alkanolamines after CO2 removal from flue gas. Issue 21 (1st November 2016) - Yin, Jun; Gao, Jie; Tong, Ming; Chen, Xin; Kang, Wanzhong; Zhou, Yanbo; Lu, Jun
ABSTRACT: The investigations of CO2 absorption rate, absorption capacity, and removal efficiency in monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA), and nonaqueous MEA solutions were carried out to improve the absorption characteristics of the absorbents. The experiments were performed using a synthetic flue gas consisting of 15% CO2 with a flow rate of approximately 0.8 L/min. It was observed that 10 wt% MEA methanol solution had the fastest CO2 absorption rate of 8.03 × 10 −5 mol/s. Furthermore, 10 wt% MEA methanol solution had the lowest regeneration temperature of 320 K.